Ethics in Oncology: Principles and Responsibilities Declared in the Italian Ragusa Statement. Issue 6 (November 2016) - Gori, Stefania; Pinto, Carmine; Caminiti, Caterina; Aprile, Giuseppe; Marchetti, Paolo; Perrone, Francesco; Di Maio, Massimo; Salè, Emanuela Omodeo; Mancuso, Annamaria; De Cicco, Maurizio; Di Costanzo, Francesco; Crispino, Sergio; et al.
Cancer care involves many ethical issues. The need for more patient-centered healthcare together with the improved empowerment of every person diagnosed with cancer have been transposed by the Italian Association of Medical Oncology (AIOM) and eventually translated in the Ragusa statement. This position paper describes the philosophy that lies beneath this document and its fundamental principles.